Integrated Airborne Particle Matter Detector - Ferlito, Umberto; Grasso, Alfio Dario; Vaiana, Michele; Bruno, Giuseppe (2019 26th IEEE International Conference on Electronics, Circuits and Systems (ICECS), 2019)
This paper describes the first results of a research project that aims to the development of a miniaturized atmospheric particulate matter sensor. The detector relies on a gravimetric selection of the particle size and on an integrated capacitive sensing interface. In this communication, in particular, preliminary results regarding the electronic readout are presented.